Unraveling the impact of food processing technologies on postbiotic bioactivity, food matrix interactions, and human health outcomes - Junxin Zhao; Mengfei Duan; Ruiying Xu; Yumeng Cheng; Jinheng Li; Deguo Wang; Xianghui Yan; Ping Yu; Zheling Zeng; Yunzhi Lin; Yoshimitsu Masuda; Ken-ichi Honjoh; et al. (Food Bioscience, 2026)

Health Effects of Occupational and Environmental Exposures to Nuclear Power Plants: A Meta-Analysis and Meta-Regression - Ro-Ting Lin; Hathaichon Boonhat; Yu-Yu Lin; Sonja Klebe; Ken Takahashi (Current Environmental Health Reports, 2024)
Purpose of Review Numerous epidemiological studies have shown increased health risks among workers and residents living near nuclear power plants exposed to radiation levels meeting regulatory dose limits. This study aimed to evaluate the association between radiation exposure and disease risks among these populations exposed to radiation levels meeting the current regulatory dose limits. Recent Findings We searched four databases (Cochrane Library, PubMed, ScienceDirect, and Web of Science) for studies published before August 2023, screened eligible studies (inclusion and exclusion criteria based on population, exposure, comparator, and outcome framework), and collected data on exposure indicators and disease risks. We applied random-effects models of meta-analysis to estimate the pooled effects and meta-regression to assess the dose-response relationship (radiation dose rate for workers and distance for residents). We identified 47 studies, 13 with worker and 34 with resident samples, covering 175 nuclear power plants from 17 countries, encompassing samples of 480,623 workers and 7,530,886 residents. Workers had a significantly lower risk for all-cancer and a significantly higher risk for mesothelioma. Residents had significantly higher risks for all-cancer, thyroid cancer, and leukemia. Notably, children under 5 years old showed the highest risk for all-cancer. Our meta-regression showed a significantly positive dose-response relationship between cumulative dose of radiation exposure and risk for circulatory disease among workers. Summary Our findings demonstrated higher risks for mesothelioma for workers and all-cancer, thyroid cancer, and leukemia for residents exposed to low-dose radiation from nuclear power plants. Some included studies did not adjust for cancer risk confounders, which could overestimate the association between radiation exposure and cancer risk and increase the risk of bias.

Single-cell lineage tracing with endogenous markers - Yan Xue; Zezhuo Su; Xinyi Lin; Mun Kay Ho; Ken H. O. Yu (Biophysical Reviews, 2024)
Resolving lineage relationships between cells in an organism provides key insights into the fate of individual cells and drives a fundamental understanding of the process of development and disease. A recent rapid increase in experimental and computational advances for detecting naturally occurring somatic nuclear and mitochondrial mutation at single-cell resolution has expanded lineage tracing from model organisms to humans. This review discusses the advantages and challenges of experimental and computational techniques for cell lineage tracing using somatic mutation as endogenous DNA barcodes to decipher the relationships between cells during development and tumour evolution. We outlook the advantages of spatial clonal evolution analysis and single-cell lineage tracing using endogenous genetic markers.

Biocontrol of Salmonella Typhimurium in milk, lettuce, raw pork meat and ready-to-eat steamed-chicken breast by using a novel bacteriophage with broad host range - Junxin Zhao; Yunzhi Lin; Chen Wang; Mahmoud Zayda; Aye Thida Maung; Tahir Noor Mohammadi; Hoang Minh Duc; Ping Yu; Maomao Ma; Deming Gong; Jun Sato; Yoshimitsu Masuda; et al. (International Journal of Food Microbiology, 2023)

Gas-phase isopropanol degradation by nonthermal plasma combined with Mn-Cu/-Al2O3 - Ken-Lin Chang; Yu-Chieh Lin; Ming-Ze Qiu; Chun-Wei Tu; Chih-Ping Chang; Jhong-Lin Wu; Yung-Chang Lin; Chien-Kuei Chang (Environmental Science and Pollution Research, 2021)

Chronic ketamine abuse is associated with orexin-A reduction and ACTH elevation - Ming-Chyi Huang; Chun-Hsin Chen; Lian-Yu Chen; Hu-Ming Chang; Chih-Ken Chen; Shih-Ku Lin; Ke Xu (Psychopharmacology, 2020)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Therapy with the Combination of Amlodipine and Irbesartan Has Persistent Preventative Effects on Stroke Onset Associated with BDNF Preservation on Cerebral Vessels in Hypertensive Rats - Yu Hasegawa; Takashi Nakagawa; Ken Uekawa; Mingjie Ma; Bowen Lin; Hiroaki Kusaka; Tetsuji Katayama; Daisuke Sueta; Kensuke Toyama; Nobutaka Koibuchi; Shokei Kim-Mitsuyama (Translational Stroke Research, 2016)

Tissue factor expression in ovarian cancer: implications for immunotherapy with hI-con1, a factor VII-IgGFc chimeric protein targeting tissue factor - Emiliano Cocco; Joyce Varughese; Natalia Buza; Stefania Bellone; Ken-Yu Lin; Marta Bellone; Paola Todeschini; Dan-Arin Silasi; Masoud Azodi; Peter E. Schwartz; Thomas J. Rutherford; Luisa Carrara; et al. (Clinical & Experimental Metastasis, 2011)

Replacement of Buried Cysteine from Zebrafish Cu/Zn Superoxide Dismutase and Enhancement of Its Stability via Site-Directed Mutagenesis - Chuian-Fu Ken; Chi-Tsai Lin; Yu-Der Wen; Jen-Leih Wu (Marine Biotechnology, 2007)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)